Material volatility: Wittgenstein's notebooks and editorial practice. Issue 7 (3rd July 2021) - Venkatesh, Vidya
ABSTRACT: The chaotic archive of unpublished notes that Wittgenstein left behind materialises the repetitious, fragmented, and inconclusive form of his philosophy. While there has been much attention paid to the practical problems posed by the material form of Wittgenstein's archive, there has been very little reflection on its theoretical and hermeneutic significance. This paper interposes discussions of proper editorial practice for Wittgenstein's Nachlass with a close analysis of one of his notebooks, MS 147. In particular, it focuses on expressive non-linguistic inscriptions in MS 147, such as emphasis and punctuation, and argues that these textual elements not only inflect the meaning of the remarks they punctuate, but also indicate an alternative hermeneutic paradigm in which to consider Wittgenstein's philosophy. It concludes that MS 147 invites a reading practice that is suppressed by dominant editorial practices, and gestures towards alternative editorial orientations.